2019
DOI: 10.1186/s12284-019-0319-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing trait contribution and mapping novel QTL for salinity tolerance using the Bangladeshi rice landrace Capsule

Abstract: Background Salinity is one of the most widespread abiotic stresses affecting rice productivity worldwide. The purpose of this study was to establish the relative importance of different traits associated with salinity tolerance in rice and to identify new quantitative trait loci (QTL) conferring tolerance to salinity at seedling stage. A total of 231 F 2:3 plants derived from a cross between a sensitive variety BRRI dhan29 (BR29 hereafter) and Capsule, a salt tolerant Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 82 publications
7
38
1
Order By: Relevance
“…The SSR markers tightly linked to these QTLs are valuable for pyramiding false smut resistance into the elite cultivars. Simple sequence repeats (SSR) are universally distributed in plant genomes and are often used as molecular markers in the genetic linkage analysis and QTL mapping (Chen et al 2017;Su et al 2018;Rahman et al 2019). In this study, a low percentage (< 5%) of SSR markers were identified to be polymorphic between the parental cultivars, which might be caused by high genetic similarity between 08R2394 and MR183-2, which are both Indica rice lines.…”
Section: Discussionmentioning
confidence: 87%
“…The SSR markers tightly linked to these QTLs are valuable for pyramiding false smut resistance into the elite cultivars. Simple sequence repeats (SSR) are universally distributed in plant genomes and are often used as molecular markers in the genetic linkage analysis and QTL mapping (Chen et al 2017;Su et al 2018;Rahman et al 2019). In this study, a low percentage (< 5%) of SSR markers were identified to be polymorphic between the parental cultivars, which might be caused by high genetic similarity between 08R2394 and MR183-2, which are both Indica rice lines.…”
Section: Discussionmentioning
confidence: 87%
“…Sun et al (2019) mapped 23 QTLs for traits related to salt stress with cultivar 'Changbai 10' as donor parent. Similarly, Rahman et al (2019) identified 20 QTLs for salt tolerance in rice using F 2 mapping population developed with a landrace 'Capsule' as donor parent. In this study, we evaluated progenies from a new donor source for salt tolerance; 'Madina Koyo' and mapped regions on the chromosomes controlling tolerance to salt stress at the early seedling stage.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on determining signi cant QTLs for drought stress tolerance, majority of the marker loci co-localized with known QTLs for blast tolerance or NBS-LRR disease resistance genes were located within the regions of signi cantly distortion levels (Dixit et al 2014). Similar observation on Bangladeshi rice landrace Capsule in relation to salt stress tolerance (Rahman et al 2019). The four parental lines used in the construction of the genetic map are known to contain traits for resistance to bacterial blight (G. davidsonii), sucking pests such as aphids (G. klotzschianum), Fusarium wilt, silver leaf white y and cotton bollworm resistance (G. thurberi), Verticillium wilt (G. trilobum).…”
Section: Discussionmentioning
confidence: 62%